On the Adventures of Democracy and Violence - Kačerauskas, Tomas (Problemos, 2006)
The author reviews the annual conference “Democracy and Violence” of Lithuanian Society of Philosophers in the year 2006. The author draws on organizational problems, summarizes every presentation, and reports a fragment of discussions. The author maintains that the conference was a significant event in Lithuanian philosophical life.